1998
DOI: 10.1177/105971239800600302
|View full text |Cite
|
Sign up to set email alerts
|

From Egocentric to Allocentric Spatial Behavior: A Computational Model of Spatial Development

Abstract: Psychological experiments on children's development of spatial knowledge suggest that experience at self-locomotion and visual tracking are important factors. Yet, the mechanism underlying development is unknown. We propose a robot that learns to track a target object mentally (i.e., maintaining a representation of an object's position when outside the field of view) as a model for spatial development. Mental tracking is considered as prediction of an object's position, given the previous environmental state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Hiraki, Sashima and Phillips (1998) proposed a computational model of spatial development. They proposed a robot that learned to track a target mentally, and demonstrated that, in the absence of the capacity for self‐locomotion, the robot made errors that were self‐centered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hiraki, Sashima and Phillips (1998) proposed a computational model of spatial development. They proposed a robot that learned to track a target mentally, and demonstrated that, in the absence of the capacity for self‐locomotion, the robot made errors that were self‐centered.…”
mentioning
confidence: 99%
“…Therefore, the effect of locomotion on spatial performance also depends on the spatial test applied. If children have to remember a spatial routine that can be solved by egocentric, self‐centered strategies, they might depend less on active locomotion during exploration than when solving an orientation test demanding the use of allocentric orientation strategies, as is suggested by the findings of Hiraki et al (1998).…”
mentioning
confidence: 99%
“…Two early implementations of simulation-like mechanisms of this kind were the "Connectionist Navigational Map (CNM)" of Chrisley (1990) and the simulated robot (arm) "Murphy" by Mel (1991). The theoretical motivation behind the connectionist navigational map was the transition from non-conceptual to conceptual knowledge [see, e.g., Barsalou (1999)], and later models have focused on, for example, allocentric spatial knowledge (Hiraki et al, 1998), learning the spatial layout of a maze-like environment [e.g., Jirenhed et al (2001) and Hoffmann and Möller (2004)], obstacle avoidance (Gross et al, 1999), and robot dreams .…”
Section: Computational Models Of Internal Simulationmentioning
confidence: 99%
“…Barsalou, 1999). Later models have investigated the following types of behaviors: a) allocentric spatial knowledge (Hiraki, et al, 1998) b) learning the topological structure of a maze like environment, identified as successful navigation, either physically or mentally (Hoffmann & Möller, 2004;Jirenhed et al 2001;Jirenhed, 2001;Nolfi & Tani, 1999;Tani & Nolfi, 1998;Svensson, Morse & Ziemke, 2009[IV]; Ziemke et al, 2005), c) goal-directed navigation: the robots are given a goal-configuration and should find the goal by using the cognitive map as internal/planning resource (Baldassarre, 2002;Hoffmann & Möller, 2004;Tani, 1996), d) obstacle avoidance (Gross et al, 1999), and e) problem solving (van Dartel, 2005) This chapter discusses some of the issues addressed by these previous computational models and also describes an approach to model the development of simulation in robots inspired by the so-called inception of simulation (InSim) hypothesis (Svensson, Thill, and Ziemke, 2013[VI]; Thill and Svensson, 2011[V]). For a more complete review of previous computational models of simulation, see (Svensson, 2007).…”
Section: Simulations Of Simulationmentioning
confidence: 99%